Edukasi Hak Kesehatan Seksual Reproduksi dan Kekerasan Gender Berbasis Seksual: Mana yang Paling Diminati Remaja? - Hilmawan, Muhammad Taufik; Meviana, Dliya Laela Eka; Amelia, Risqi Falah; Pramusti, Selvia Ratih (Griya Widya: Journal of Sexual and Reproductive Health, 2023)
Background: Adolescents are particularly vulnerable to inadequate access to knowledge about sexual and reproductive health rights (HKSR) and gender-based violence (KBGS). This lack of knowledge often leads to misinformation, poor health outcomes, and increased vulnerability to sexual and gender-based violence. Despite efforts to improve HKSR education, many adolescents, especially in rural and underserved areas, continue to face significant barriers in accessing reliable information and services. Objective: The purpose of this study was to examine the level of knowledge and awareness of HKSR and KBGS among adolescents and to identify the factors that contribute to their vulnerability in accessing this knowledge. Method: This research employed a quantitative approach with a descriptive observational method. Data were collected through surveys administered to adolescents in various regions, focusing on their knowledge, attitudes, and access to HKSR and KBGS information and services. Result: The study revealed that 72.4% of adolescents had limited knowledge about HKSR and KBGS. The primary factors contributing to this knowledge gap included lack of comprehensive sexuality education in schools (45.3%), cultural taboos surrounding discussions of sexual and reproductive health (30.6%), and limited access to health services (24.1%). Conclusion: The findings indicate that inadequate education and cultural barriers significantly impact adolescents' access to HKSR and KBGS information. To address this issue, it is crucial to implement comprehensive sexuality education programs in schools, promote open discussions about sexual and reproductive health, and improve access to health services for adolescents. Addressing these factors can help reduce the vulnerability of adolescents to misinformation and improve their overall health and well-being.